Development of a novel, windowless, amorphous selenium based photodetector for use in liquid noble detectors. (1st January 2023) - Rooks, M.; Abbaszadeh, S.; Asaadi, J.; Febbraro, M.; Gladen, R.W.; Gramellini, E.; Hellier, K.; Blaszczyk, F. Maria; McDonald, A.D.
Abstract: Detection of the vacuum ultraviolet (VUV) scintillation light produced by liquid noble elements is a central challenge in order to fully exploit the available timing, topological, and calorimetric information in detectors leveraging these media. In this paper, we characterize a novel, windowless amorphous selenium based photodetector with direct sensitivity to VUV light. We present here the manufacturing and experimental setup used to operate this detector at low transport electric fields (2.7–5.2 V/μm) and across a wide range of temperatures (77 K–290 K). This work shows that the first proof-of-principle windowless amorphous selenium device is robust under cryogenic conditions, responsive to VUV light at cryogenic temperatures, and preserves argon purity. These findings motivate a continued exploration of amorphous selenium devices for simultaneous detection of scintillation light and ionization charge in noble element detectors.